3(2x-1)-4(4x+2)=0

Simple and best practice solution for 3(2x-1)-4(4x+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)-4(4x+2)=0 equation:


Simplifying
3(2x + -1) + -4(4x + 2) = 0

Reorder the terms:
3(-1 + 2x) + -4(4x + 2) = 0
(-1 * 3 + 2x * 3) + -4(4x + 2) = 0
(-3 + 6x) + -4(4x + 2) = 0

Reorder the terms:
-3 + 6x + -4(2 + 4x) = 0
-3 + 6x + (2 * -4 + 4x * -4) = 0
-3 + 6x + (-8 + -16x) = 0

Reorder the terms:
-3 + -8 + 6x + -16x = 0

Combine like terms: -3 + -8 = -11
-11 + 6x + -16x = 0

Combine like terms: 6x + -16x = -10x
-11 + -10x = 0

Solving
-11 + -10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -10x = 0 + 11

Combine like terms: -11 + 11 = 0
0 + -10x = 0 + 11
-10x = 0 + 11

Combine like terms: 0 + 11 = 11
-10x = 11

Divide each side by '-10'.
x = -1.1

Simplifying
x = -1.1

See similar equations:

| X-235/25=-1.2816 | | 3X/4.5=1/8 | | 10x+3y+2z-3y= | | 28-4x-20=-4 | | x-4+8x=60 | | 3-7n+5n=7-52 | | 1.6x+0.25(16-x)=0.26(-16) | | x=5+3x | | 5.379+3.001x=10.429 | | 4y-9+y+46=8y+40-6y | | 5(2x-4)=4(2x+1) | | 8+0.09x=14 | | 14-2.2x=-8 | | -16+7k=k-2k | | 6x+3+2x=5x-4 | | -16k+7k=k-2k | | 7.2x-4.9=60.1 | | (32x^2-8x+4)=0 | | 3/7-3x | | (x+5)(x+2)=25 | | 5x^2+2Y^2+2xy-2x-4y+2=0 | | 4x+5+2x+12=180 | | 2x^2+5y^2=16 | | a^2+b^2=625 | | 7(z+3)-3z=44 | | 10+15y=3y | | Sin(3x)+sin(9x)= | | 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 |

Equations solver categories